2012
DOI: 10.1073/pnas.1213820109
|View full text |Cite
|
Sign up to set email alerts
|

Genome streamlining and chemical defense in a coral reef symbiosis

Abstract: Secondary metabolites are ubiquitous in bacteria, but by definition, they are thought to be nonessential. Highly toxic secondary metabolites such as patellazoles have been isolated from marine tunicates, where their exceptional potency and abundance implies a role in chemical defense, but their biological source is unknown. Here, we describe the association of the tunicate Lissoclinum patella with a symbiotic α-proteobacterium, Candidatus Endolissoclinum faulkneri, and present chemical and biological evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
207
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(209 citation statements)
references
References 45 publications
1
207
0
1
Order By: Relevance
“…The detection of this candidate genus from a GBR ascidian expands the known geographic range of this symbiont taxon and further supports its specificity to the host genus Ecteinascidia. In addition, this symbiont lineage is particularly notable for its putative role in secondary metabolite synthesis within the animal cell, including the production of the anticancer agent ET-743 (Rath et al, 2011), which may constitute a key functional aspect of ascidian-bacterial symbioses (Kwan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of this candidate genus from a GBR ascidian expands the known geographic range of this symbiont taxon and further supports its specificity to the host genus Ecteinascidia. In addition, this symbiont lineage is particularly notable for its putative role in secondary metabolite synthesis within the animal cell, including the production of the anticancer agent ET-743 (Rath et al, 2011), which may constitute a key functional aspect of ascidian-bacterial symbioses (Kwan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As a basal lineage in the phylum Chordata, ascidians occupy a key stage in deuterostome evolution (Delsuc et al, 2006). Ascidians are also a prolific source of novel marine natural products (Erwin et al, 2010) and the involvement of microbial symbionts in bioactive compound production (Schmidt and Donia, 2010) has prompted recent studies of the ascidian microbiota (Donia et al, 2011;Kwan et al, 2012). Historically, most studies of microbial symbionts in ascidians have focused on cyanobacteria, in particular the genera Prochloron and Synechocystis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there are several examples in which a defensive role has been experimentally assigned to individual secondary metabolites (Paul et al, 1990;Joullie et al, 2003). Strikingly, there are now several examples in which it has been shown that symbiotic bacteria produce potentially defensive metabolites, while the host animals do not (Supplementary Table S8) (Schmidt et al, 2005;Donia et al, 2006Donia et al, , 2008Rath et al, 2011;Donia et al, 2011bDonia et al, , 2011cKwan et al, 2012). Beyond defense, symbiotic metabolites in ascidians are also known to have other roles.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, certain groups of highly toxic polyketides are synthesized by genome-reduced, obligate intracellular alpha-proteobacteria, Candidatus Endolissoclinum faulkneri (Kwan et al, 2012). This interaction has resulted in vertical transmission and co-speciation that has been ongoing for approximately 6-35 million years (Kwan et al, 2012;Kwan and Schmidt, 2013). During that period, the production of toxic secondary metabolism has been maintained while the remainder of the symbiont's genome has degraded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation